2023
DOI: 10.1172/jci170191
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptomic analysis of renal allograft rejection reveals insights into intragraft TCR clonality

Abstract: Bulk analysis of renal allograft biopsies (rBx) identified RNA transcripts associated with acute cellular rejection (ACR); however, these lacked cellular context critical to mechanistic understanding of how rejection occurs despite immunosuppression (IS). We performed combined single-cell RNA transcriptomic and TCR-α/β sequencing on rBx from patients with ACR under differing IS drugs: tacrolimus, iscalimab, and belatacept. We found distinct CD8 + T cell phenotypes (e.g., effector, memory… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 53 publications
(70 reference statements)
0
13
0
Order By: Relevance
“…A third possibility is that CD8 EXP clonotypes are cross-reactive, recognizing both recipient HLA:viral peptide ligands and simultaneously recognizing donor HLA peptides in the context of donor HLA presentation, as recently demonstrated in a mouse heart transplantation model (68). Although prior studies on kidney allograft rejection defined the intragraft CD8 EXP as alloreactive (37), it remains possible that some of the CD8 UNEXP T cell clones within our dataset are either directly alloreactive or contribute to the alloresponse by providing costimulatory 'help' to alloreactive CD8 EXP clones, as recently shown in a mouse skin transplantation model (69). The avidity, allospecificity, viral peptide cross-reactivity, and potential cooperation between CD8 EXP vs. CD8 UNEXP T cell clones is a subject of ongoing investigation utilizing human CDR3-expressing Jurkat 76 T cell lines recently described by our group (37).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A third possibility is that CD8 EXP clonotypes are cross-reactive, recognizing both recipient HLA:viral peptide ligands and simultaneously recognizing donor HLA peptides in the context of donor HLA presentation, as recently demonstrated in a mouse heart transplantation model (68). Although prior studies on kidney allograft rejection defined the intragraft CD8 EXP as alloreactive (37), it remains possible that some of the CD8 UNEXP T cell clones within our dataset are either directly alloreactive or contribute to the alloresponse by providing costimulatory 'help' to alloreactive CD8 EXP clones, as recently shown in a mouse skin transplantation model (69). The avidity, allospecificity, viral peptide cross-reactivity, and potential cooperation between CD8 EXP vs. CD8 UNEXP T cell clones is a subject of ongoing investigation utilizing human CDR3-expressing Jurkat 76 T cell lines recently described by our group (37).…”
Section: Discussionmentioning
confidence: 91%
“…Single cell RNA sequencing analysis of adult kidney allograft rejection has recently revealed that a limited number of expanded CD8 + T cell clones (CD8 EXP ) are found in the tissue and urine during ACR and that these expanded clones persist in the tissue after rejection treatment, changing their gene expression profiles in response to differing immunosuppressive regimens (37). Similar findings were recapitulated in bronchioalveolar lavage fluid from rejecting lung transplant recipients (38).…”
Section: Introductionmentioning
confidence: 99%
“…Altogether, our novel findings support the hypothesis that CD8 T cells are candidate targets to treat TCMR more effectively and this postulate is also supported by our finding that the fraction of CD8 T cells is the highest among graft infiltrating T-cell subsets (Figure 9) and the recent finding from the scRNA-Seq study that CD8 T are the dominant T-cell subtype in the rejecting kidney allograft. 58 CD8 Treg have been described, 59 and CD8 targeting, therefore, should be undertaken with appropriate immune monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Results of this work have raised intriguing questions about the capacity of donor-reactive T cells infiltrating kidney grafts to mediate acute rejections in patients treated with either tacrolimus, belatacept, or blocking anti-CD40 monoclonal antibody iscalimab maintenance immunosuppression. 7 The authors isolated cells from biopsies of 10 kidney grafts at the time of acute T cell-mediated rejection and several times after treatment for the rejection episode. Combined single-cell RNA sequencing and sequencing of both TcR α and β chains provided a thorough functional transcriptomic picture of the effector functions expressed by infiltrating innate and T-cell populations within the rejecting grafts.…”
mentioning
confidence: 99%
“…A study from Shi et al 7 has provided new mechanistic insights to answer these important questions. Results of this work have raised intriguing questions about the capacity of donor-reactive T cells infiltrating kidney grafts to mediate acute rejections in patients treated with either tacrolimus, belatacept, or blocking anti-CD40 monoclonal antibody iscalimab maintenance immunosuppression.…”
mentioning
confidence: 99%